Effect of Probenecid on Endothelial Cell Growth Rate and Retinal Angiogenesis in an Oxygen-Induced Retinopathy Model - Jiang, Jingbo; Ou, Weiming; Luo, Xianqiong; Xiang, Jianwen; Liu, Guosheng; Huang, Shuiqing; Li, Hongping; He, Longkai; Gan, Jiamin; Han, Shasha; Nie, Chuan (Frontiers in Pharmacology, 2021)
Objectives: Probenecid is an anion transport inhibitor, which, according to the connectivity map (CMap; a biological application database), interferes with hypoxia-induced gene expression changes in retinal vascular endothelial cells (ECs). Here, we investigated the influence of probenecid on retinal ECs cytotoxicity and retinal neovascularization in a murine oxygen-induced retinopathy (OIR) model. Methods: Retinal ECs growth rate in the presence of hypoxia-mimicking concentrations of cobalt chloride (CoCl2) was determined using the thiazolyl blue tetrazolium bromide (MTT) assay and proliferating cell nuclear antigen (PCNA) expression. In OIR rats, probenecid was administered by intraperitoneal injection (i. p.) from postnatal day (P) 1 to P7. The concentrations of vitreous humor vascular endothelial growth factor (VEGF), hypoxia-inducible factor (HIF)-1α, and placental growth factor (PlGF) were determined by ELISA at P21. The amount of newly formed vascular lumen was evaluated by histopathological examination. Retinopathy and neovascularization were assessed by scoring isolectin B4 fluorescein-stained retinal flat mounts. Western blots for liver tissue HIF-1α and hepcidin (HAMP) were performed. Results: In vitro, probenecid led to the recession of hypoxia-induced EC growth rate. In vivo, compared to the OIR retina, upregulation of VEGF, HIF-1α, and PlGF in phase II retinopathy of prematurity (ROP) was inhibited by probenecid administration. Moreover, probenecid ameliorated neovascularization and resulted in significantly reduced relative leakage fluorescence signal intensity in fluorescence-stained retinal flat mounts (P < 0.05). Probenecid alleviated the liver overactivation of HAMP and downregulation of HIF-1α in the OIR rats. Conclusions: This is the first demonstration that probenecid may be a protective compound against retinal angiogenesis in OIR. These changes are accompanied with decreased hyperoxia-mediated hepcidin overproduction. Although the relevance of the results to ROP needs further research, these findings may help to establish potential pharmacological targets based on the CMap database.